A naturalistic study of herbal medicine for self-reported depression and/or anxiety a protocol - David Casteleijn; Amie Steel; Diana Bowman; Romy Lauche; Jon Wardle (Integrative Medicine Research)
Background: Mental health conditions including anxiety and depression account for around 8% of the global disease burden. Anxiety and depression often coexist and impose a high individual and social burden. Patients with mental and behavioural conditions may be at increased risk of co-morbidities and are often high health-care utilisers. Herbal medicine is estimated to be used by up to 80% of the worlds population, and by 22% of Australian women seeking care for depression. The holistic and tailored treatment approach offered by practitioners of herbal medicine is difficult to capture in randomised controlled trials and as such there is a paucity of research demonstrating the outcomes of real-life practice. This project aims to address this gap with a whole practice, observational model. Methods: The study will employ a naturalistic observational design. Two-hundred patient participants will be recruited to be treated by 15 clinician participants from different naturopathic clinics. The observed changes in anxiety and depression symptoms of patients will be documented across three consultations using validated patient-reported outcome measures (SF-36, DASS-21, GHQ-28 and POMS-2). Discussion: Clinical studies investigating the efficacy of individualised herbal medicine treatment as prescribed by a naturopath are rare. Our study attempts to fill this gap with a longitudinal observation of individualised care as practiced by naturopaths in Australia; to offer valuable insights into the effectiveness of individualised herbal medicine practice and provide contextualisation of data currently focused on individual herbal medicines in specific conditions. Trial Registration: Australian and New Zealand Clinical Trials Registry: ACTRN12616000010493 Keywords: Anxiety, Complementary medicine, Depression, Individualised western herbal medicine, Naturopathy